Horse´s gait motion analysis system based on videometry - Torres-Pérez, Yolanda; Gómez-Pachón, Edwin Yesid; Cuenca-Jiménez, Francisco (Universidad Pedagógica y Tecnológica de Colombia, 2016)
In this work, we describe the development and use of a new motion analysis system to investigate and evaluate 2D kinematic of the equine gait. This system uses a motion capture software, mathematical calculations, and a graphic interface designed to evaluate locomotor patterns of the horses. From video sequences of equine motion recorded by high-speed cameras, we obtained the coordinates (x, y) using TEMA 3.0 software; then, we calculated kinematic variables such as length of body segments, joint’s angles, trajectories of each marker, and joint flexion-extension curves; and with a graphical interface developed in the Mathematica software, we generated a 2D simulation of the horses movement. This tool aims at helping to investigate and evaluate the equine gait, and analyze it in an objective way (qualitative and quantitative); However, it can be used in different fields of gait analysis. This tool removes the subjectivity of the diagnosis made by veterinarians, and allows to perform different analyses, evaluations, researches, and monitoring of the equine gait.